Comparative evaluation of relaxant effects of three prangos species on mouse corpus cavernosum: Chemical characterization and the relaxant mechanisms of action of P. pabularia and (+)-oxypeucedanin. (10th February 2022) - Sevin, Gulnur; Alan, Elif; Demir, Serdar; Albayrak, Gokay; Demiroz, Tugce; Yetik-Anacak, Gunay; Baykan, Sura
Abstract: Ethnopharmacological relevance: Erectile dysfunction (ED) is the most common form of sexual dysfunction which has been the topic of great interest through the history by all cultures. It is now among the most treated health problems in men of all ages that develop under the influence of lifestyle factors and some diseases. Plants are extensively used to cure sexual dysfunction for centuries. Roots of Prangos sp. have been used to improve sexual performance in Anatolian traditional medicine and are rich of coumarin, furanocoumarin and their derivatives. Scientific research is necessary to support and validate the ethno-traditional uses of these plants. Aim of the study: The aim of this study is to investigate the effects of the root extracts of P. pabularia, P. uechtritzii and P. heyniae on erectile function and to isolate and identify the chemical compounds of the most active extract and reveal possible pharmacological mechanism of the major compound of the extract with the strongest relaxant effect in mouse corpus cavernosum (MCC). Materials and methods: The roots of plants were extracted with chloroform, n -hexane and methanol. The compounds were isolated from the extract by column chromatography and structures were identified by NMR and MS. The relaxant effects of extracts (10 −7 -10 −4  g/mL), (+)-oxypeucedanin (10 −7 -10 −4  M) and Na2 S (10 −7 -3 × 10 −3  M) were tested in MCC strips by DMT myograph. To investigate the mechanism, the synthesis inhibitors of aminooxyacetic acid (AOAA, 10 −2  M) and nitro-L-arginine methyl ester (L-NAME, 10 −4  M) were used, respectively. H2 S formation was evaluated basal and L-cysteine (L-cyst)-stimulated conditions by H2 S microsensor. Results: All extracts relaxed MCC in a concentration dependent manner. The maximum relaxing effects were achieved with chloroform extracts. Chloroform extract of P. pabularia (Pp-CE) was more potent than the others. Pp-CE-induced relaxations were significantly decreased by AOAA and L-NAME. (+)-Oxypeucedanin, the major compound of Pp-CE, induced relaxant responses and this effect was inhibited by AOAA, but not L-NAME. The relaxation of (+)-oxypeucedanin was found to be similar in view of Emax to positive control H2 S donor Na2 S. (+)-Oxypeucedanin increased L-cyst-stimulated H2 S formation. Augmentation of H2 S synthesis with (+)-oxypeucedanin was inhibited by AOAA. Conclusions: Pp-CE has the strongest effect on relaxation of MCC and this result supports the traditional aphrodisiac use of P. pabularia root extract in Anatolia. The pharmacological mechanisms of Pp-CE to relax MCC involve NO and H2 S formation. (+)-Oxypeucedanin could be responsible for the H2 S-mediated relaxations of Pp-CE in MCC. Graphical abstract: Image 1 Highlights: n -hexane, chloroform and methanol extracts of Prangos pabularia Lindl., Prangos uechtritzii Boiss & Hauskn and Prangos heyniae H. Duman & M. F. Watson relax MCC and the maximum relaxing effects were achieved with chloroform extracts. The relaxant response to extract of P. pabularia in MCC is more potent than P. uechtritzii and P. heyniae. P. pabularia relaxes MCC by stimulating NO and H2 S synthesis. (+)-Oxypeucedanin, a major compound of P. pabularia, is responsible for the H2 S-related relaxant effect in MCC.